Miscarriage and Anti TPO antibodies - Pradhan, Santosh; Gautam, Keyoor (Journal of Pathology of Nepal, 2018)
Autoimmune thyroid disorders are common in women of reproductive age. Anti-TPO antibody and thyroglobulin antibody are frequently found to be associated. Anti-TPO antibodies are responsible for the activation of complement and are thought to be significantly involved in thyroid dysfunction. In early pregnancy women with anti TPO antibodies are prone to develop subclinical or overt hypothyroidism leading to adverse obstetric and fetal outcomes. An association between the risk of a miscarriage and anti TPO antibodies has also been reported even in absence of overt thyroid dysfunction. However, screening for these antibodies and Levothyroxin supplement in anti TPO antibodies -positive euthyroid pregnant women has not been established yet.